A Bibliometric on Cost Management and Financial Efficiency - Loso Judijanto; Ikhyanuddin Ikhyanuddin (Westscience Press, 2026)
This study aims to systematically map and analyze the global research landscape on cost management and financial efficiency using a bibliometric approach. Drawing on bibliographic data retrieved from the Scopus database, the study applies network and visualization techniques using VOSviewer to examine publication trends, influential literature, thematic structures, and collaboration patterns among authors, institutions, and countries. The findings reveal that the intellectual core of the field is dominated by themes related to costs, efficiency, cost–benefit analysis, and financial management, reflecting strong foundations in accounting and performance measurement. Over time, the research focus has evolved toward sustainability-oriented and technology-driven themes, including energy efficiency, sustainable development, artificial intelligence, blockchain, and risk management. Collaboration analysis shows a highly centralized global structure, with the United States and China acting as major hubs and elite institutions playing key roles in knowledge production. This study provides a comprehensive overview of the evolution and structure of cost management and financial efficiency research, offering valuable insights for scholars and practitioners while highlighting opportunities for future research that integrates sustainability, digital transformation, and broader international collaboration.